Mitigating the risk of inflammatory type primary graft dysfunction by applying an integrated approach to assess, modify and match risk factors in lung transplantation - Braithwaite, Sue A.; Berg, Elize M.; de Heer, Linda M.; Jennekens, Jitte; Neyrinck, Arne; van Hooijdonk, Elise; Luijk, Bart; Buhre, Wolfgang F. F. A.; van der Kaaij, Niels P. (Frontiers in Transplantation, 2024)
Long-term outcome following lung transplantation remains one of the poorest of all solid organ transplants with a 1- and 5-year survival of 85% and 59% respectively for adult lung transplant recipients and with 50% of patients developing chronic lung allograft dysfunction (CLAD) in the first 5 years following transplant. Reducing the risk of inflammatory type primary graft dysfunction (PGD) is vital for improving both short-term survival following lung transplantation and long-term outcome due to the association of early inflammatory-mediated damage to the allograft and the risk of CLAD. PGD has a multifactorial aetiology and high-grade inflammatory-type PGD is the result of cumulative insults that may be incurred in one or more of the three variables of the transplantation continuum: the donor lungs, the recipient and intraoperative process. We set out a conceptual framework which uses a fully integrated approach to this transplant continuum to attempt to identify and, where possible, modify specific donor, recipient and intraoperative PGD risk with the goal of reducing inflammatory-type PGD risk for an individual recipient. We also consider the concept and risk-benefit of matching lung allografts and recipients on the basis of donor and recipient PGD-risk compatibility. The use of ex vivo lung perfusion (EVLP) and the extended preservation of lung allografts on EVLP will be explored as safe, non-injurious EVLP may enable extensive inflammatory testing of specific donor lungs and has the potential to provide a platform for targeted therapeutic interventions on lung allografts.